International Congress on Polymers in Concrete (ICPIC 2018) Polymers for Resilient and Sustainable Concrete Infrastructure (Springer International Publishing, 2018)
This volume collects the proceedings from the International Congress of Polymers in Concrete 2018 (ICPIC), held under the theme "Polymers for Resilient and Sustainable Concrete Infrastructure." ICPIC 2018 provides an opportunity for researchers and specialists working in the fields of polymers to exchange ideas and follow the latest progress in the use of polymers in concrete infrastructure. It also showcases the use of polymers and polymer concrete in sustainable and resilient development, and provides a platform for local and overseas suppliers, developers, manufacturers and contractors using polymers, polymer concrete and polymer composites in concrete structures to develop new business opportunities and follow the latest developments in the field. The International Congress of Polymers in Concrete is an international forum that has taken place every three years for the last 40 years with the objective of following progress in the field of polymers and their use in concrete and construction. Following 15 successful congresses held in London (1975), Austin (1978), Koriyama (1981), Darmstadt (1984), Brighton (1987), Shanghai (1990), Moscow (1992), Oostende (1995), Bologna (1998), Honolulu (2001), Berlin (2004), Chuncheon (2007), Funchal (2010), Shanghai (2013) and Singapore (2015), the 16th ICPIC will take place in Washington, DC, from April 29 to May 1st, 2018.